2013
DOI: 10.1177/1756283x13493878
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic neuroendocrine tumors: approach to treatment with focus on sunitinib

Abstract: Pancreatic neuroendocrine tumors (pNETs) are relatively rare malignancies. With secretory tumors such as insulinomas, vasoactive intestinal peptideomas, and gastrinomas, the hormone produced causes the symptom complex (e.g. hypoglycemia, peptic ulcer disease). With nonsecretory NETs, the clinical condition is determined by tumoral growth and metastasis. The course of metastatic pNETs may be indolent for several years but progression is often more rapid at later stages, leading to significant disability and a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 77 publications
(104 reference statements)
1
18
0
1
Order By: Relevance
“…Sunitinib malate is an oral, multitargeted tyrosine kinase inhibitor of VEGF receptors 1, 2, and 3, PDGFRs α and β, stem-cell factor (KIT) receptor, FMS-like tyrosine kinase 3, colony-stimulating factor 1 receptor, and glial cell line-derived neurotrophic factor receptor [121]. The antitumor activity of sunitinib in PNETs was shown in a phase III study.…”
Section: Systemic Medical Managementmentioning
confidence: 98%
“…Sunitinib malate is an oral, multitargeted tyrosine kinase inhibitor of VEGF receptors 1, 2, and 3, PDGFRs α and β, stem-cell factor (KIT) receptor, FMS-like tyrosine kinase 3, colony-stimulating factor 1 receptor, and glial cell line-derived neurotrophic factor receptor [121]. The antitumor activity of sunitinib in PNETs was shown in a phase III study.…”
Section: Systemic Medical Managementmentioning
confidence: 98%
“…Three different oral regimens of vandetanib (A: ascending doses of 300 --1200 mg or placebo; B: crossover design of 300 mg under fed and fasting conditions and [14] C: vandetanib 800 mg), were studied in healthy volunteers in order to investigate metabolism, excretion and elimination routes in a previous study [38]. Mean t 1/2 time in all regimens was 215.8 --246.6 h (19 days on average).…”
Section: Healthy Subjectsmentioning
confidence: 99%
“…The above findings indicate VEGFR-2 signaling as a key regulator in tumor pathogenesis. VEGFR-2 appears to be an eligible target for novel therapeutic approaches, and currently several new anticancer agents, including TKI targeting VEGFR-2, are already in use in daily clinical practice, while several others are being developed or tested in clinical trials [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A trial evaluating the efficacy of sunitinib in PanNETs showed that the progression free survival in the treatment group was more than double that of the control group, demonstrating the promise of this therapeutic approach. 118, 119 . Other drugs targeting angiogenesis such as bevacizumab and pazopanib are currently under study in PanNETs.…”
Section: Advances In Therapymentioning
confidence: 99%